The fall of Constantinople in 1453 AD and the impact in Europe - مرعي, سعد (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Constantinople is one of the most important global cities due to its distinguished location, it was surrounded by sea water on three sides, the Bosphorus Strait from the east, the sea of Marmara from the south, and the Golden Horn from the north, on the land side, it was protected by its high walls, When the Muslims entered into jihad with the Byzantine state, this city had a role in this conflict. The caliphs of the Muslims fantasized about the necessity of seizing them. To conquer Constantinople at the hands of a man, let the prince be its prince, and yes the army is that army, but it withstood the repeated attacks of Muslims until the ottomans came at the beginning of the eighteenth century Ah when they succeeded the Seljuk state of Rome, where the ottoman attempts to control it began during the reign of Sultan Bayazid 1, whose forces managed to Constantinople was besieged in 1393 AD, but he lifted its siege as a result of the Mongol invasion of the lands of the ottoman Empire until the reign of Sultan Muhammad 11, who was able during his reign to seize Constantinople and make it the capital of the ottoman Empire, which had a great impact on the European countries, which felt the approach of the ottoman threat to them.